Tambulin Targets Histone Deacetylase 1 Inhibiting Cell Growth and Inducing Apoptosis in Human Lung Squamous Cell Carcinoma - Wang, Wuming; Liu, Yuzhen; Zhao, Long (Frontiers in Pharmacology, 2020)
There is an urgent unmet need to develop new therapeutics for lung squamous cell carcinoma (LSCC) as the current gold standard treatment regimens are dominated by chemotherapy. In this study, we observed the treatment effects of the natural compound tambulin on LSCC and explored its mechanism of action. LSCC cell lines H226 and H520 were cultured in vitro to observe the effects of tambulin on cell proliferation and apoptosis. Western blotting was used to detect the expression of histone deacetylase 1 (HDAC1) and apoptosis-related proteins. Cell derived xenografts (CDX) of H226 and H520 in nude mice were established to examine the inhibitory effects of tambulin in vivo. Results showed that tambulin inhibited the proliferation of H226 and H520 cells in a dose-dependent manner and inhibited the growth of CDX tumors. Tambulin also promoted the apoptosis of H226 and H520 cells, up-regulated the protein expression of cleaved caspase-3, cleaved caspase-9 and Bax, and down-regulated HDAC1 and Bcl-2 protein expression. In support of this, immunohistochemical analysis of CDX tumors from mice treated with tambulin showed increased expression of cleaved caspase-3 and Bax, while the expression of HDAC1 and Bcl-2 were decreased. What's more, when HDAC1 was over-expressed via adenovirus transduction in H226 or H520 cells, the effects of tambulin were significantly attenuated. Interestingly, we found that combining tambulin with cisplatin treatment in CDX models was more effective than single drug treatment, suggesting that tambulin may enhance the sensitivity of LSCC to cisplatin. Taken together, this study proves that tambulin has a definite therapeutic effect on LSCC. Mechanistically, tambulin downregulates HDAC1, which in turn regulates the Bcl-2/caspase signaling pathway and promotes cancer cell apoptosis.